Change in the family food environment is associated with positive dietary change in children - Hendrie Gilly; Sohonpal Gundeep; Lange Kylie; Golley Rebecca (International Journal of Behavioral Nutrition and Physical Activity, 2013)
Abstract Background The family food environment is an important influence in the development of children’s dietary habits. Research suggests that influences of current dietary behaviour and behaviour change may differ. The aims of this paper were to: (1) investigate the association between the food environment at baseline and change in children’s saturated fat intake; and (2) to explore whether a change in the food environment was associated with a change in children’s saturated fat intake. Method Secondary analysis of a 12 week cluster randomised controlled trial in 133 4-13 year old children. Families were randomly allocated to parental education regarding changing to reduced-fat dairy foods or a comparison non-dietary behaviour. The interventions were family focused. Parents received education from a dietitian in 3x30minute sessions to facilitate behaviour change. Parents completed a comprehensive questionnaire capturing three domains of the food environment – Parent knowledge and attitudes; shaping practices; and behaviours and role modelling. Children’s dietary intake was assessed via multiple 24-hour recalls at baseline and week 12. Changes in the family food environment and primary outcome (saturated fat) were calculated. Hierarchical linear regression models were performed to explore the association between baseline and change in food environment constructs and change in saturated fat intake. Standardised Beta are presented (p<0.05). Results After adjustments for child and family demographics, higher levels of perceived food availability (β=-0.2) at baseline was associated with greater reduction in saturated fat intake, where as higher perceived responsibility (β=0.2), restriction (β=0.3) and pressure to eat (β=0.3) were associated with lesser change in saturated fat. An increase in nutrition knowledge (β=-0.2), perceived responsibility (β=-0.3) and restriction (β=-0.3) from baseline to week 12 were associated with greater reduction in saturated fat intake. Conclusions The present study was one of the first to quantify changes in the family food environment, and identify a number of factors which were associated with a positive dietary change. Because interventions focus on behaviour change, the findings may provide specific targets for intervention strategies in the future. Trial registration Australia New Zealand Clinical Trials Registry ACTRN12609000453280.